TINJAUAN PERENCANAAN SALURAN PRIMER DAERAH IRIGASI D.I TANJUNG DURIAN KABUPATEN PASAMAN BARAT - Surya Edy; Surya Eka Priana; Ana Susanti Yusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
As the population increases, the demand for water increases. This condition is very concerning for farmers because irrigation buildings are not functionally good enough to meet the water needs of plants and buildings that are already inadequate if the river water rises during the rainy season it will overflow and cannot be accommodated by the irrigation canal, it is necessary to make a good irrigation system in the rainy season. Tanjung Durian irrigation area which is in the preparation village opposite the West Pasaman Regency. The area of the irrigation watershed is 375 ha and the canal under review is the primary canal with a length of 612 m. The researcher conducted a primary channel review by collecting primary data. for data processing, researchers use the Harspers method and the Gumbel method, the calculation of hydraulic analysis is to use the calculation of rainfall data for the last 10 years. From the results of the study, it was found that the calculation of the dimensions of the existing channel in the field did not meet the requirements because the Qmax value of 12.84 m3/s was greater than the field Q value of 5.607 m3/s from the existing plan in the field, so that the water overflowed when there was a flood in the channel. The results of the research plan obtained that the planned Q value of 17.808 m3/s is greater than the Qmax value of 12.84 m3/s. Observations of researchers need to improve the quality of the dam in the Tanjung Durian irrigation canal, because the dam still uses gabion wire Keywords : Primary Canal, Irrigation, Hasrpers Method, Gumbel Method